BUILDING SMART CLASSROOMS: UTILIZING TECHNOLOGY TO ENHANCE SOCIAL STUDIES EDUCATION - Fuji Rahayu; Aramudin (Universitas Islam Negeri Mataram, 2025)
In this digital era, technology plays a crucial role in education, particularly in the teaching of SocialStudies. This article aims to explore how the utilization of technology in building smart classrooms canenhance the quality of learning in Social Studies subjects. The research employs a descriptive qualitativemethodology, utilizing literature studies and interviews with educators and education experts. Thefindings indicate that the use of technology, such as advanced hardware, educational applications, andthe internet, can enhance student interactivity, broaden access to learning resources, and create moreengaging and compelling learning experiences. By optimally integrating technology, smart classroomscan help students better understand complex Social Studies concepts through more dynamic andinteractive media. This research concludes that technology can be a highly effective tool for enrichingSocial Studies education, and its proper application will positively impact education as a whole